Illiquidity Premium and Monetary Conditions in Emerging Markets: An Empirical Examination of Taiwan Stock Markets - Chen, Chia-Cheng; Tai, Chia-Li; Liu, Yi-Sheng (International Journal of Economics and Financial Issues, 2019)
This study empirically examines the illiquidity premium of Taiwan stock markets and its relationship with monetary policies. We find that commonly used illiquidity measures are generally sensitive and capable of capturing market illiquidity, particularly during the most volatile periods. Evidence shows that unconditional illiquidity is significantly priced across three illiquidity measures during the sample period. Aggregate market illiquidity innovations are noticeably affected by monetary policies. The results of Granger causality tests reveal that expansive monetary policy improves market illiquidity, whereas restrictive policy adversely affects market liquidity. Keywords: Illiquidity; illiquidity premium; monetary policy; asset pricing; Granger’s causality tests JEL Classifications: G11, G12, G15 DOI: https://doi.org/10.32479/ijefi.8953